EVALUATION OF WEB CONTENT TECHNOLOGIES IN LIBRARIES OF SELECTED INSTITUTIONS OF NATIONAL IMPORTANCE IN INDIA - Negi, Dheeraj Singh; Pandey, Praveen Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focused on Evaluation of web content selected National Institute of Importance Libraries in India. This study based on Including the three aspects, every aspect consists of various elements examined based on the information on the library website. The General information, Library Collection and Library feature that IIT Delhi library scored 7 out of 8, after the data analysis evaluates the various feature of the website and webpages of selected libraries with the selected criteria. The website has found to get updated. All the selected Institution have a proper library webpage. This study finds out that IIT Delhi library web content and advance technology using in own services. School of Architecture and Planning Delhi website some features are not available Keyword Search (70%) is the most commonly available feature, ensuring efficient resource discovery. Registration/Login, Download Forms, Feedback, and Layout (each at 30%) are moderately implemented, indicating a focus on accessibility and user interaction, though not universally adopted. However, Navigation (10%) and Direct Links (20%) have limited presence, suggesting potential difficulties in website usability. Notably, Social Networking 20%.